Minimizing Open‐Circuit Voltage Loss in Perovskite/Si Tandem Solar Cells via Exploring the Synergic Effect of Cations and Anions. Issue 12 (16th May 2021) - He, Yongcai; Tang, Zeguo; Mao, Lin; Yang, Shaofei; Yang, Tian; Xie, Minghui; Chang, Qing; Ding, Lei; He, Bo; Peng, Chenwei; Yu, Cao; Hao, Xia; et al.
Abstract : A high‐efficiency of 25.9% for perovskite/Si heterojunction tandem solar cells is achieved with an open‐circuit voltage of 1.74 V contributed by ≈1.02 and ≈0.72 V from the top and bottom cells, respectively. The results demonstrate that the addition of methylammonium chloride (MACl) effectively mitigates the open‐circuit voltage loss in the perovskite cell, where the MA cation tunes the bandgap while the Cl anion facilitates grain growth with less boundaries. Meanwhile, the excess lead iodide (PbI2 ) caused by the evaporation of MACl plays a beneficial passivation role to achieve high open‐circuit voltage. The performance of the tandem solar cells is a synergic consequence of all cations and anions considering the thickness, bandgap, phase stability, and defect in the perovskite absorber. Abstract : A high‐efficiency of 25.9% for a perovskite/Si heterojunction tandem cell is achieved with an open‐circuit voltage of 1.74 V contributed by ≈1.02 and ≈0.72 V from the top and bottom cells, respectively. The performance of the tandem cells is a synergic consequence of all cations and anions considering the bandgap, phase stability, and defect in the perovskite.